(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2023)
The research proposes an innovative plan for the development of reading comprehension in the teaching work from virtuality in students of the fourth grade of the Educational Institution Presbítero Álvaro Suarez, it is proposed as a general objective "Analyze the skills of reading comprehension in the teaching work of primary basic education from virtuality". The methodology is guided by the quantitative approach, descriptive type and field design, the research sample was represented by 40 students and three teachers for a total of 43, The technique is the survey and the data were analyzed by statistical analysis. Finally, it is concluded that ICT supports the motivation of reading comprehension in students.